PARAFFIN PROBLEM TREATING ALONG THE FLOWLINE (STUDY CASE: FROM WELLHEAD “X” TO THE SEPARATOR”) - Herianto Herianto (SINERGI, 2018)
Paraffin deposition becomes a problem in the crude oil transportation system in surface production facilities, especially in oilfield flowline. The cause is big pressure drop which can inhibit the fluid flow rate. Paraffin problem occurrence is affected by specific factors, such as crude oil characteristics, flowing pressure and oil temperature drop below the oil pour point. From the parameter mentioned before, the potential of experiencing paraffin deposition in the flowline from the wellhead to the separator needs to be analyzed. From the physical properties analysis, paraffin deposition occurs when the temperature is decreased below the oil pour point (43 OC). In this case, the wellhead temperature is 65 OC. Paraffin problem countermeasures are being done by installing insulation along the flowline to resolve the fluid heat loss. If the previous countermeasure method could not solve the problem, a sand heater is needed to be installed to heat up the fluid inside the flowline in a certain point of distance.